Physical chemical characteristics of cooled raw milk under federal inspection (Research, Society and Development, 2020)
Milk production requires a series of steps to obtain this product with quality, this work aims to verify the current legislation and describe the physicochemical tests performed on milk, based on federal legislation, each of the steps to obtain the proper milk for consumption. Milk must meet the basic hygienic-sanitary quality requirements and the physicochemical standards, and also undergo the entire heat treatment without undergoing organoleptic changes ensuring all the nutritional characteristics of this product for safe consumption, free of pathogenic microorganisms. ensuring safety to public health. This article had as research method conducted through literature survey, the legislation and quality parameters required by animal product inspection bodies. Thus, it was observed that there is a need for a reevaluation of Normative Instruction 62, as it is not reaching the quality standards required in obtaining milk.